Factors Influencing Income of Micro and Small Enterprises In Minahasa Regency - Sinolungan, Alzefin YRM; Kimbal, Rahel Widiawati (International Journal of Applied Business and International Management, 2024)
Research Objective is to determinie the Effect of Bussiness Capital, Bussiness Location, Training and Product Promotion together on the Income of Micro and Small Bussinesses in Minahasa Regency. Theoretically,the Facto’s Affecting Income of Micro and Small Enterprises in Minahasa Regency.Small Micro (Producer’s or Seller’s,namely whether or not a Trader is able to Influence Buyer’s of Mechandise and Services (Consumer’s) or Buyer’s and get the Expected Result’s. Data used: Primary Data and Secondary Data.The Analysis  Tool used is Multiple Regression Analysis. Research Business Locations: there are 25 Minahasa Districts, where the Minahasa Regency Research Business Loactions have a Positive and Significat Effect On The Business Income of Micro-Small Business Actor’s in Minahasa Regency,so that it has the Effect of being able to increase the Income of Micro-Small Business actor’s in Minahasa Regency